The Great Recession And Increased Cost Sharing In European Health Systems. - Palladino,R; Lee,JT; Hone,T; Filippidis,FT; Millett,C (Health Aff (Millwood), 2016)
European health systems are increasingly adopting cost-sharing models, potentially increasing out-of-pocket expenditures for patients who use health care services or buy medications. Government policies that increase patient cost sharing are responding to incremental growth in cost pressures from aging populations and the need to invest in new health technologies, as well as to general constraints on public expenditures resulting from the Great Recession (2007-09). We used data from the Survey of Health, Ageing and Retirement in Europe to examine changes from 2006-07 to 2013 in out-of-pocket expenditures among people ages fifty and older in eleven European countries. Our results identify increases both in the proportion of older European citizens who incurred out-of-pocket expenditures and in mean out-of-pocket expenditures over this period. We also identified a significant increase over time in the percentage of people who incurred catastrophic health expenditures (greater than 30 percent of the household income) in the Czech Republic, Italy, and Spain. Poorer populations were less likely than those in the highest income quintile to incur an out-of-pocket expenditure and reported lower mean out-of-pocket expenditures, which suggests that measures are in place to provide poorer groups with some financial protection. These findings indicate the substantial weakening of financial protection for people ages fifty and older in European health systems after the Great Recession.